Deciphering amyotrophic lateral sclerosis: What phenotype, neuropathology and genetics are telling us about pathogenesis. Issue 1 (May 2013) - Ravits, John; Appel, Stanley; Baloh, Robert H.; Barohn, Richard; Rix Brooks, Benjamin; Elman, Lauren; Floeter, Mary Kay; Henderson, Christopher; Lomen-Hoerth, Catherine; Macklis, Jeffrey D.; McCluskey, Leo; Mitsumoto, Hiroshi; et al.
Abstract Amyotrophic lateral sclerosis (ALS) is characterized phenotypically by progressive weakness and neuropathologically by loss of motor neurons. Phenotypically, there is marked heterogeneity. Typical ALS has mixed upper motor neuron (UMN) and lower motor neuron (LMN) involvement. Primary lateral sclerosis has predominant UMN involvement. Progressive muscular atrophy has predominant LMN involvement. Bulbar and limb ALS have predominant regional involvement. Frontotemporal dementia has significant cognitive and behavioral involvement. These phenotypes can be so distinctive that they would seem to have differing biology. However, they cannot be distinguished, at least neuropathologically or genetically. In sporadic ALS (SALS), they are mostly characterized by ubiquitinated cytoplasmic inclusions of TDP-43. In familial ALS (FALS), where phenotypes are indistinguishable from SALS and similarly heterogeneous, each mutated gene has its own genetic and molecular signature. Overall, since the same phenotypes can have multiple causes including different gene mutations, there must be multiple molecular mechanisms causing ALS − and ALS is a syndrome. Since, however, multiple phenotypes can be caused by one single gene mutation, a single molecular mechanism can cause heterogeneity. What the mechanisms are remain unknown, but active propagation of the pathology neuroanatomically seems to be a principal component. Leading candidate mechanisms include RNA processing, cell-cell interactions between neurons and non-neuronal neighbors, focal seeding from a misfolded protein that has prion-like propagation, and fatal errors introduced during neurodevelopment of the motor system. If fundamental mechanisms could be identified and understood, ALS therapy could rationally target progression and stop the disease − a goal that seems increasingly achievable.